Integrasi Model DeLone & McLean, UTAUT, dan HOT-Fit untuk Menilai Keberhasilan dan Keberterimaan Aplikasi LPD Mobile di Bali - Dewangga, Anak Agung Bagus Dharma Putra; Ariyanto, Dodik; Wirakusuma, Made Gede; Sujana, I Ketut (Jurnal Sistem Informasi Bisnis, 2025)
Transparency challenges faced by Village Credit Institutions (LPDs) in Bali pose a significant risk to the future reputation of these institutions. In response to this challenge, LPDs introduced the LPD Mobile application to improve operational transparency. However, not all LPDs in Bali have yet implemented this system, so an in-depth analysis is needed to assess the extent of its success and acceptance from a user perspective. The integrated model used in this study is a combination of the DeLone & McLean, UTAUT, and HOT-Fit models with the addition of one moderating variable, namely education level, with the aim of identifying key factors that influence the success and acceptance of LPD Mobile. Through hypothesis testing using Partial Least Squares Structural Equation Modelling (PLS-SEM) method on 384 customers in 106 LPDs, all hypotheses were supported and the study found that education level, as a moderator variable, strengthens the influence of human factors on behavioral intentions. Technological factors emerged as the most influential on user satisfaction, while organizational factors showed a lesser impact on behavioral intentions. This integrated model successfully dissect the elements that influence the success and acceptance of LPD Mobile adoption in Bali. The results of this study can be used by LPDs in Bali to plan the direction of LPD development towards technological aspects, while future studies can explore this conceptual framework in different regions or countries with different microfinance institutions, organizational maturity levels, and cultural contexts, thus providing new insights into the flexibility and generalisability of this model.